2019
DOI: 10.1016/j.vaccine.2018.11.081
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccine uptake in men who have sex with men in Scotland

Abstract: Human papillomavirus (HPV) vaccines are currently utilised globally in national immunisation programmes. In July 2017, a national HPV vaccine programme for men who have sex with men (MSM) was initiated across Scotland with vaccine being offered in the sexual health clinic setting. During the first year of this targeted vaccination programme, there were 5,905 individuals who received at least one dose of HPV vaccine, representing 63.7% of eligible MSM attendees in this period. Vaccine uptake was relatively stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…[37][38][39][40][53][54][55] While improved screening strategies are essential for successful AIN prevention programmes, patient participation is equally important. 56 For this reason, further efforts should be made to encourage both male and female PLWH to take part in screening and prevention programmes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39][40][53][54][55] While improved screening strategies are essential for successful AIN prevention programmes, patient participation is equally important. 56 For this reason, further efforts should be made to encourage both male and female PLWH to take part in screening and prevention programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we suggest that HPV vaccination especially for MSM and PLWH with high‐risk behaviour should be a part of future prevention strategies . While improved screening strategies are essential for successful AIN prevention programmes, patient participation is equally important . For this reason, further efforts should be made to encourage both male and female PLWH to take part in screening and prevention programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, once a successful HPV-vaccination program for girls has been established, targeted HPV vaccination for MSM appears as the next priority for the prevention of HPV-related malignancies [27]. Pollock et al [28] recently studied the HPV vaccine uptake in MSM in Scotland in an opportunistic program, with vaccination being offered in the sexual health clinic setting. They concluded that the first-dose uptake was moderately high, but suggested that gender-neutral immunization would be preferable to MSM-targeted vaccination, reducing stigma and inequality.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of free HPV vaccination provided by national programs was 37.6% among MSM in the United States [24], 42.6% in Australia [21], 49.1% in England [25], and 63.7% in Scotland [20]. HPV vaccination uptake among the male population is very low in Hong Kong [26], and previous studies have reported zero uptake among MSM [27,28].…”
Section: Introductionmentioning
confidence: 85%
“…As a result, the US Centers for Disease Control and Prevention (CDC) recommends MSM who are in the age range of 45 years or below to receive HPV vaccination [13,18]. Free national HPV vaccination programs for MSM aged up to 45 years attending sexual health and HIV clinics rolled out in England and Scotland in 2018 and 2017, respectively [19,20]. The Victorian Government of Australia funded a free time-limited HPV vaccination catch-up program for MSM aged up to 26 years in 2017 [21].…”
Section: Introductionmentioning
confidence: 99%